PROFESSIONALISM DEVELOPMENT OF FOREIGN LANGUAGE TEACHER OF TECHNICAL HIGHER EDUCATIONAL ESTABLISHMENT IN THE SELF-ACTUALIZATION PROCESS - Абсалямова, Я. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
The article explains the essence and importance of professionalism development of foreign language teacher of technical higher educational establishment in the self-actualization process. It defines directions for further studies. The article proves that professional development of the teachers’ category is intensive at all stages of their self-actualization